Children After Cancer? Meeting Male Patients' Fertility Needs During Cancer Care - María Belén Herrero; Peter T.K. Chan (European Medical Journal, 2018)
The prospect of cancer survivorship has changed significantly in the past decades. Cancer patients are now living longer and healthcare professionals are increasingly aware of the concerns of survivors with regard to quality of life. It is well known that psychological and social problems are created or exacerbated by cancer. At any stage of cancer survivorship, individuals may experience depression, a high sense of vulnerability, fear for the future, and other types of worries, such as changes in sexual function and reproductive ability. For many survivors, the ability to conceive and deliver a healthy baby is of paramount importance. However, in many circumstances, and for a variety of complex reasons, the importance of fertility is under-addressed and sometimes disregarded by the healthcare team. This article describes the significance of addressing fertility as a psychosocial need in male cancer patients, followed by a discussion on cancer patients' and family members' perceptions about the importance of fertility preservation. The authors also present practical strategies to improve the quality of services for cancer patients to address their fertility needs.